Public announcement logic in cryptographic protocol / Muhammad Farhan Mohd Nasir - Muhammad Farhan , Mohd Nasir (2019)
Public announcement logic with common knowledge (PAC) is a logic that formalizes the notion of epistemic update. The main objective of this study is to propose a labelled natural deduction proof system for PAC and to show some applications of PAC in the cryptographic protocol. We begin by modifying the Kripke model that is capable of giving semantics to formulas having announcement indexing. Then, a labelled natural deduction for PAC (NPAC) is proposed and its soundness and completeness are proven. Then, we proved its normalization using a proof-theoretic semantical notion of validity of a derivation. Finally, an application of PAC in cryptographic protocol is presented.